Curcumin Gel Versus Chlorhexidine Gel for Treatment of Chronic Gingivitis Associated with Fixed Orthodontic Appliance - Hussein, Sawsan Ramadhan; Rashid, Sherzad Khorsheed (Science Journal of University of Zakho, 2023)
Background and aims: Gingivitis in orthodontic treatment remains a challenging and undesirable consequence of orthodontic treatment. Hence, a variety of chemical or herbal agents, methods, and techniques have been investigated to prevent or reduce gingivitis that occurs in orthodontic treatment. In this study, we will evaluate and compare the effect of curcumin (CMN) gel with chlorhexidine (CHX) gel on clinical parameters (plaque and gingival index) and oral bacterial number (total bacterial count test) in fixed orthodontic patients that have gingivitis. We are the first to use curcumin gel for patients that have gingivitis with fixed orthodontic appliances. Samples and Methods: Forty-five patients with fixed orthodontic appliances with metallic brackets that have generalized chronic dental plaque-induced gingivitis were selected randomly and divided into three groups - Group I (control), Group II (CMN), and Group III (CHX), respectively. Clinical parameters which are plaque index (PI) and gingival index (GI) were recorded at the baseline, 14 days, and 21 days of treatment, and a total bacterial count test (TBCT) was done for all the participants before and after treatment. Results: Both Curcumin and Chlorhexidine gel groups showed a significant reduction (P0.05). Conclusion: The results of this study show that curcumin and chlorhexidine gel have comparable anti-plaque, anti-gingivitis, and antibacterial activities and that both can be used to effectively treat plaque-induced gingivitis.
Keywords: Curcumin gel; Chlorhexidine gel; dental plaque-induced gingivitis; orthodontic treatment; anti-plaque; anti-inflammatory; anti-microbial effect